2022
DOI: 10.3390/ijms23115955
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of H2S-Releasing Molecules in an In Vitro Model of Sarcopenia: Relevance of Glucoraphanin

Abstract: Sarcopenia is a gradual and generalized skeletal muscle (SKM) syndrome, characterized by the impairment of muscle components and functionality. Hydrogen sulfide (H2S), endogenously formed within the body from the activity of cystathionine-γ-lyase (CSE), cystathionine- β-synthase (CBS), and mercaptopyruvate sulfurtransferase, is involved in SKM function. Here, in an in vitro model of sarcopenia based on damage induced by dexamethasone (DEX, 1 μM, 48 h treatment) in C2C12-derived myotubes, we investigated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
(110 reference statements)
1
3
0
Order By: Relevance
“…Moreover, a recent published study by Micheli et al [ 53 ] showed in vitro results that are in accordance with the in vivo results we report. They established a Dex-induced sarcopenia in an in vitro model in C2C12-derived myotubes; they studied the role of exogenous and endogenous H2S sources.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a recent published study by Micheli et al [ 53 ] showed in vitro results that are in accordance with the in vivo results we report. They established a Dex-induced sarcopenia in an in vitro model in C2C12-derived myotubes; they studied the role of exogenous and endogenous H2S sources.…”
Section: Discussionsupporting
confidence: 93%
“…H 2 S is an important gasotransmitter with known cardioprotective effects [8][9][10]. H 2 S has been reported to be released from the enzymatic degradation products of some GSLs, i.e., ITCs, in physiological conditions [15,27,28]. This study explored the antioxidant effects of GSLs in cardiac cells and examined the possible utility of H 2 S signaling in mediating the functions of GSLs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, natural H 2 S donors existing in plants have shown remarkable biological activity. To date, there is a large body of literature showing the beneficial effect of natural products as H 2 S releasers, such as glucoerucin, glucoraphanin, diallyl trisulfide (DATS), and diallyl disulfide (DADS) occurring in rocket, cruciferous vegetables, or garlic [32][33][34][35][36][37]. Alongside these compounds, many other small natural molecule polysulfides have received attention as equally or more active sources of H 2 S or alternatively viable reservoirs of sulfane sulfur through the transsulfuration pathway [38].…”
Section: Introductionmentioning
confidence: 99%